Moderating role of Gender and Family Income on Green Entrepreneurial Intention factors: An empirical study on Higher Education Students (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
As the world becomes green, it emphasizes  the importance of adopting a sustainable,  environmentally and socially beneficial lifestyle.  A growing body of academic research on “going  green” offers a new standpoint on the concept of  Green Entrepreneurship. Green entrepreneurship  aims to follow classic entrepreneurial ideals while  providing additional benefits to society and the  environment at the same time. The study explores  the influence of factors, namely, entrepreneurial  creativity, university green entrepreneurial  support, green recognition, and green value  variables, on green entrepreneurial intentions,  along with the moderating role of gender, family  income and family occupation among students. Data from 600 Undergraduate and Postgraduate  students was collected using the survey method.  For this purpose, a structured questionnaire  with a five-point Likert scale was used. The  statistical techniques applied to the dataset  were confirmatory factor analysis and structural  equation modeling using SPSS, AMOS, and  process-Macro.
Keywords: Green entrepreneurship; Environmental Values; University green entrepreneurial support; Higher education; Green Value; Green recognition